Literary theory, comparative literature and translation studies: routes and intersections - Sales Salvador, Dora (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This essay aims at accounting for the intersections and mediations that articulate most of the present developments in the fields of literary theory, translation theories and comparative literature. If translation is, more than ever, an “interdiscipline”, it is also true that, On the trail of the “cultural turn” of literary theory and comparative literature, translation plays a role of great importance, We start from the liminal zone of the Polysystem Theory, which —since its emergence in the seventies— has been and continues to be essential for comparative literature and its consolidation as an autonomous discipline, while at the same time it has also been an active thrust for translation studies since the eighties. Reflecting upon the de-centralizing impregnation of the transcultural literary systems, mainly immersed in the postcolonial sphere, we will observe how the complex interlinguistic and intercultural dialogue which shapes them is a necessary communicative bridge in the global reality which surrounds us, where, above all, itis crucial to learn to assume and rethink our differences.